Indonesian efforts to overcome covid-19's effects on its municipal solid waste management: a review. Issue 1 (31st December 2022) - Budihardjo, Mochamad Arief; Humaira, Natasya Ghinna; Putri, Soraya Annisa; , Syafrudin; Yohana, Eflita; Ramadan, Bimastyaji Surya; Zaman, Badrus; Sutrisno, Endro
Abstract: The COVID-19 pandemic has worsened the solid waste management problem in Indonesia. Lockdowns induced by the pandemic have increased waste generation. Meanwhile, the COVID-19 virus continues to spread through droplets and items exposed to such droplets, including solid waste. Therefore, it is necessary to have exceptional municipal waste management systems in place to ensure these contaminants do not negatively impact the environment, society, or waste workers. We reviewed the municipal waste management systems during the COVID-19 pandemic in Indonesia and suggested remediation of several practices. Several problems exist in the current system, such as increase in solid waste generation (especially food and plastic waste), lack of infectious waste management, many workers not using complete personal protective equipment (PPE) while handling waste, and an inequitable distribution of facilities across different cities. Comprehensive recommendations, such as citizen awareness, PPE use by waste workers and waste pickers, and government policies dealing with urban waste amid the COVID-19 pandemic, are discussed. The findings of this study can serve as a reference for municipal waste management under pandemic conditions in developing countries, as well as for future research.